A reparação do dano ambiental na desapropriação agrária sancionatória: A utilização de instituto do direito agrário como instrumento jurídico para a proteção ambiental - ESTABILE, Henrique César da Rocha (2010)
The Brazilian Federal Constitution, promulgated on 1988, provides the property right; nevertheless it‟s related to a social purpose. Therefore the Magna Carta asserts that the right to a healthy or adequate environment is itself a human right, which leads to the citzens and the State the responsibility of ensuring the needs and interests of present and future generations fully safeguarded, covering a variety of issues including protection of the environment. Furthermore, the Union has the authority to determine land expropriation of the areas which are not committed with a social purpose, featuring these lands for agrarian reform. Hence, knowing both constitutional guidelines, comes to a closer discussion the compensation for the environmental when there‟s a land expropriation penalty. Focusing this, an analyses could be done in a way that using the land expropriation penalty could be a legal instrument leading to environmental protection. Considering the procedures of land expropriation penalty, the expropiating entity checks the rural property including the environmental damage of it. Thus, if environmental damage is found, the State should mention demand for restitution of the area in the expropriation procedures, under penalty of handle it hereafter, counting as damage to the treasury. Moreover, there was verified the real legal intent of this kind of expropriation. In this way, it suggests a new designation of the institute and formulated a new concept of Desapropriação Agrária Sancionatória. In this inquiry, we adapt the a deductive technique, using a literature research, judicial precedents and legislative. The process used is the positivism, mitigated by Miguel Reale in Teoria Tridimensional do Direito , referring not only, in norms and brazilian courts decisions, but in historical and contemporary facts, as well as moral questions raised as instrument used in the description of the object of study.